The Problem of Subjective Value Judgment - Michael Hüther (Wirtschaftsdienst)
Abstract In the political debate about the right Western reaction to Russia’s war of aggression in Ukraine, an immediate gas embargo is being discussed and demanded in addition to the sanctions that have already been decided. The aim is to increase the economic pressure on Russia in order to end the war more quickly. Economic expertise is also needed here in order to advise politicians by making the possible economic costs and risks for Germany transparent. Doing so will disclose the unavoidable subjective value judgements. The limits of macroeconomic models must be discussed in a differentiated manner, and microeconomic findings as well as institutional conditions must be adequately acknowledged.